Sharia Banks Integration and Diversification in Asian and Middle East Countries - Helma Malini; Djihan Islahiyah (Faculty of Economics, Universitas Sriwijaya, 2019)
The growth of Sharia Banking in Indonesia shows that Sharia banking in Indonesia is not only an international hub for Sharia banking in other regions but also as a place for investors to diversify investment portfolios other than conventional banking. The certainty of Sharia banking in term of stability makes Sharia Banking in Indonesia connected to one another. However, opportunities for portfolio diversification to Sharia banks in this case; Indonesia, Malaysia, India, Qatar, Bahrain and Japan are in questioned on whether there is integration between Sharia banking in those region and whether there is a possibility of Diversification of Sharia banking Portfolios in the region. In this manner the study is analysed on 25 banks’ data across selected countries. In the present study, ROA (Return on Assets) and ROE (Return on Equity) are used as measure of performance of diversification of banks. The number of credits and the amount of credits that Sharia banks let borrowers’ use are employed as control variables. According to the result of the analysis showed Indonesia Sharia banks Integration with another Sharia banks in selected countries are varied based the geographical proximity and bilateral trading relation with selected countries.